Unlocking housing wealth through mortgage debt: do patterns and motivations vary by age? - Ong ViforJ, Rachel; Phelps, Christopher (2024)
Successive waves of house price appreciation have prompted homeowners to tap into housing wealth, increasing mortgage debt to meet spending needs. This paper addresses three questions about equity borrowing behaviour via panel-data modelling. First, how do homeowners’ asset and debt portfolios affect equity borrowing behaviour? Second, is equity borrowing influenced by financial behaviours relating to saving, planning and risk-taking? Third, do equity borrowing drivers vary by age? Our findings confirm that equity borrowing is generally influenced by asset and debt portfolios, with notable age-related differences. Younger homeowners exhibit greater sensitivity to changes in primary home value and debt, and risk willingness. Income, labour force status and ownership of other property are crucial for those aged 55–64, while homeowners aged 65+ are generally insensitive to asset, debt or income changes. We discuss policy implications, emphasizing the prospects of longer working lives among pre-retirees, the need for safeguards for elderly equity-borrowers, and the welfare consequences of later-life debt burdens or homeownership loss.